Associations between self-reported symptoms of SARS-CoV-2 and dietary supplement use over the previous year during the first pandemic wave. (9th January 2023) - Ellis, Amy; Bui, Chuong; Ferguson, Christine; Azarmanesh, Deniz; Park, Han-A
Abstract: During the initial wave of the COVID-19 pandemic, symptoms of infection varied widely among adults younger than 60 years. This cross-sectional investigation of adults ages 18–59 years explored associations between SARS-CoV-2 symptomatology and supplementation of micronutrients involved in immune function, such as multivitamins, vitamin D, vitamin C, vitamin E and zinc. Between August and December 2020, an online survey was completed by 287 respondents, averaging 33⋅3 ± 10⋅5 years, who recovered from SARS-CoV-2 infection within the previous 4 months. In regression models, intake of supplements over the previous year was not protective against number of symptoms or symptom severity. Despite higher rates of supplementation over the previous year, smokers experienced more symptoms and greater symptom severity than non-smokers. Micronutrient supplementation did not protect young adults from experiencing symptoms of SARS-CoV-2, but our results suggest that smoking cessation may be a more effective modifiable lifestyle factor.